Analisis Kinerja Keuangan dan Stabilitas Makroekonomi terhadap Profitabilitas PT. BCA Syariah - Aldi, Vinadya (Jurnal Ilmiah Ekonomi Islam, 2023)
The main objective of this research is to examine how financial ratios and macroeconomic stability affect the profitability of PT. BCA Syariah from 2015 to 2023. This study uses simple Ordinary Least Squares (OLS) regression and non-probability sampling to collect data. According to the findings of this study, the CAR and NPF variables have no effect on the profitability (ROA) of PT. BCA Syariah. FDR and GDP have a positive and large influence on ROA, in contrast, inflation has a negative and significant influence on PT BCA Syariah. This study has an R-square value of 0.949841, showing that each explanatory variable in the model can explain 95% of the variation of PT. Bank BCA Syariah, while the rest of it is explained by variables outside the model.